2013
DOI: 10.1111/aas.12167
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound measurement of subglottic diameter and an empirical formula for proper endotracheal tube fitting in children

Abstract: US-measured OD-ETT at SD was in good agreement with the actual OD-ETT, suggesting that US-measured SD helps in choosing the appropriate ETT diameter for children. In children older than 12 months, the equation 'OD (mm) = 0.01 × age (months) + 0.02 × height (cm) + 3.3' may help select the appropriate ETT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(68 citation statements)
references
References 22 publications
(48 reference statements)
3
64
0
1
Order By: Relevance
“…[6] Few studies have validated and evaluated the use of USG for the selection of appropriate size ETT based on subglottic diameter. [5789] Till date, no prospective randomized study have compared the age-based formula to that of USG-based method for prediction of appropriate size uncuffed ETT. Hence, we attempted to compare the age-based modified Cole's formula with that of ultrasound-guided assessment of subglottic diameter in determining the appropriate uncuffed ETT size in children undergoing surgical procedures under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Few studies have validated and evaluated the use of USG for the selection of appropriate size ETT based on subglottic diameter. [5789] Till date, no prospective randomized study have compared the age-based formula to that of USG-based method for prediction of appropriate size uncuffed ETT. Hence, we attempted to compare the age-based modified Cole's formula with that of ultrasound-guided assessment of subglottic diameter in determining the appropriate uncuffed ETT size in children undergoing surgical procedures under general anesthesia.…”
Section: Introductionmentioning
confidence: 99%
“…The use of USG to predict appropriate ETT size in children has been previously studied (6)(7)(8)(9). These studies differ from each other, as shown in Table 3.…”
Section: Discussionmentioning
confidence: 99%
“…Visualisation of the paediatric subglottic airway diameter by ultrasonography (USG) can enable a practitioner to better predict ETT size, preventing unnecessary tube changes and airway trauma. Several studies have investigated ideal cuffed tube size selection in paediatric patients; however, all these studies, including those where ultrasonographic measurements were performed (6)(7)(8)(9), selected the initial ETT size according to age-based formulas. However, other than Bae et al (6), who investigated uncuffed tube size, none of these studies actually involved initial placement of an ETT according to ultrasonographic measurements.…”
Section: Introductionmentioning
confidence: 99%
“…The ETT size determined by sonographic measurement of the minimal transverse diameter at the caudal cricoid cartilage showed the highest rate of agreement with the outer diameter of the reference ETT. With this finding we can confirm the measuring position of comparable studies: Shibasaki and colleagues used the lower edge of the cricoid cartilage for their measurements at 0 mbar; Bae and colleagues used the cricoid arch at 10 mbar; Gupta and colleagues measured at the cephalic half of the cricoid cartilage with a slow inspiratory flow in awake patients; and Kim and colleagues performed the measurements between the bilateral margins of the mid‐cricoid cartilage beyond the air‐mucosa interface at 0 mbar.…”
Section: Discussionmentioning
confidence: 99%